Educação matemática inclusiva: musicalidade, modificabilidade cognitiva estrutural e mediação docente - Gomes, Herica Cambraia (2017)
With the advancement of neuroscience, we find ourselves in a promising moment for inclusive mathematics, which has significant repercussion in the learning of the Decimal Numbering System, mainly in the associative aspects of mathematical cognition and psychomotor stimulation as inseparable in the body and mind relation. Musicality is presented as an innate process, in a construct of elements that encompass Corporeity, Rhythm and Sound, as a possibility of a new teaching strategy. Therefore, this investigation chose to identify teacher’s perception by elaborating, developing and analyzing teaching experiences of the Decimal Numbering System with Musicality in the first two years of Primary Education. The theoretical anchorage in composed of concepts that unfold into triads deriving from Neuroscience (SNARC effect, Numerical Route and Numerical Reasoning), Executive Functions (Voluntary Attention, Operational Memory and Inhibitory Control), Musicality (Corporeity/Watchful Hearing; Movements/Rhythms; and Qualities/Sound) and Teaching Mediation (Intentionality/Reciprocity. Meaning and Transcendence). The research, using a qualitative method, unfolds itself into practical activities, analyzed from the contributions of Musicality in the Decimal Numbering System teaching, into the curriculum and into teaching mediation. The results showed three improvements in teaching: 1) Voluntary Attention and Operational Memory brought by Musicality through watchful hearing projected in the Counting and in the Mental Calculation accomplished by the students, without distinction; 2) the development of the Corporeity and Musicality Scheme for Mental Calculation, in which the representation of the numerical writing comes from the Global Praxis, following systematized, coordinated, enlarged and ascending steps; and 3) the accomplishment of Mental Calculation during the Musicality activities that associate numbers and pulses, tones of musical instruments and mathematical operations, working as a process of evaluating Decimal Numbering System learning. The teacher’s self-evaluation elected studying practice, autonomy and creativity as the main influences of Musicality in the teaching performance; the teachers pointed out, also, the perspective of “error” as a boosting mechanism for the learning process and the respect of individual times as an inclusive practice of Mathematics Teaching